Bahasa dan Keterampilan Komunikasi: Metode “Talking Stick” dalam Meningkatkan Keberanian Berbicara Siswa Kelas II - Lusi Ardina Purba; Vinnauli Silalahi; Winijar Parman Tampubolon; Radode Kristianto Simarmata (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Speaking skills are one of the essential language abilities that students must possess in order to communicate effectively and express their opinions. However, many students still lack confidence when speaking in class. To address this issue, the researcher applied the Talking Stick method in the learning process. This study employed Classroom Action Research (CAR) consisting of four stages: planning, action, observation, and reflection. The research was conducted at SD Negeri 095550 Pematangsiantar in the 2025/2026 academic year with 12 students (6 male students and 6 female students) as participants. Data were collected through observation. Initially, students appeared shy and passive in expressing their opinions. However, after the implementation of the Talking Stick method, improvement was observed. In the first cycle, students showed interest and started to participate. In the second cycle, they became more confident. By the third cycle, students were active and fluent in speaking in front of the class. The results of the study indicate that the Talking Stick method effectively enhances students' speaking skills. This method encourages students to be more active, confident, and willing to express their thoughts.